Presunzioni giuridiche nell'ambiento dell diritto matrimoniale sostanziale nel codice di diritto canonico del 1983 - Góralski, Wojciech ("Iustitia et iudicium" ; 1, 2010)
In the CIC/1983 the legislator stipulates a series of presumptions pursuant to which, based on specified premises, certain facts are taken for granted. These dispositions of the Codfe have a particular significance in the area of matrimonial law. This article discusses presumptions made in the following canons: 1060; 1061; 1086; 1096; 1101; 1101; 1138; 1150 and 1152 paying particular attention to the presumption of canon 1096 which pertains the validity of marriage in dubio